2009
DOI: 10.1002/rra.1311
|View full text |Cite
|
Sign up to set email alerts
|

Parameters determining water temperature of a proglacial stream: The Phelan Creek and the Gulkana Glacier, Alaska

Abstract: The heat budget of a proglacial stream, Phelan Creek, from the Gulkana Glacier, Alaska, is estimated by using the hourly time series of stream water temperature, discharge and meteorology obtained in the summer of 2006. As an analytical result, the net shortwave radiation and bed friction occupied 32.1 and 38.2% of the total thermal input to the stream, respectively. The time series of the water temperature were simulated by a deterministic model with the coupling of the heat budget and the thermal advective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 10 publications
7
53
2
Order By: Relevance
“…Measured albedo values for streams with higher SSC were similar to values found in past work from high‐turbidity settings. Mean albedo values for streams with SSC greater than 50 mg/L averaged 0.10, which is consistent with the values reported by Chikita et al () on a highly turbid proglacial river where SSC typically exceeded 200 mg/L. Measurements from Lillooet River were nearly identical to those found in previous work by Knudson () on the same river.…”
Section: Discussionsupporting
confidence: 89%
“…Measured albedo values for streams with higher SSC were similar to values found in past work from high‐turbidity settings. Mean albedo values for streams with SSC greater than 50 mg/L averaged 0.10, which is consistent with the values reported by Chikita et al () on a highly turbid proglacial river where SSC typically exceeded 200 mg/L. Measurements from Lillooet River were nearly identical to those found in previous work by Knudson () on the same river.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the highly turbid water and the dependence of SSC on discharge at Phelan Creek, Chikita et al . () characterised the albedo as a constant value of 0.1, based on albedometer measurements. Richards and Moore () found that SSC at the outlet of Place Lake was consistently between about 60 and 100 mg/L, and did not exhibit a clear relation with discharge, in contrast to the situation at Phelan Creek.…”
Section: Discussionmentioning
confidence: 96%
“…Mean water temperature and the relative magnitude of daily thermal variation were broadly similar to Arctic systems at lower latitudes, although the maximum summer temperature was approximately 9 °C lower in Svalbard (79°N) than in Alaskan rivers located between 66°N and 69°N (Irons and Oswood, ; Chikita et al ., ). Water temperature was lower in all of the study rivers when compared with those recorded in alpine environments (Uehlinger et al ., ; Brown et al ., ; Cadbury et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although precipitation inputs were minimal throughout the monitoring season, subperiods with higher precipitation coincided with lower water and air temperatures. Discharge trends were not affected by precipitation events, as documented previously in other glacial basins and elsewhere (Brown et al ., ; Brown & Hannah, ; Chikita et al ., ), most likely because the volume of precipitation during each rainfall event in Svalbard was much lower than typically experienced in alpine regions (Brown and Hannah, ). Such low precipitation inputs are unlikely to have directly induced cooler river temperature by heat advection, as noted by Brown and Hannah ().…”
Section: Discussionmentioning
confidence: 99%